Determinants of innovation in a small open economy: a multidimensional perspective - Carvalho, Luísa; Costa, Teresa; Caiado, Jorge (Journal of Business Economics and Management, 2013)
This paper uses logistic regression analysis to examine how intramural and extramural R&D, acquisition of machinery, equipment and software, acquisition of external knowledge, training, market introduction and other procedures and technical preparations determine the innovation behaviour of manufacturing and service firms. We adopt a multidimensional view of innovation by considering product, process, organizational and marketing innovations as dependent variables separately. The study reports on the Community Innovation Survey (CIS4) of a small open-economy country. The empirical results indicate that intramural R&D has a positive impact on innovation. In contrast, the influence of extramural R&D on innovation is unclear. All innovation activities contribute towards organizational innovation. The study also suggests that there are no significant differences between services and manufacturing firms concerning the propensity to innovation.